Primary hypothyroidism and autoimmune thyroiditis alter the transcriptional activity of genes regulating neurogenesis in the blood of patients - Bilous Iryna I. (Sciendo, 2021)
Objective. Thyroid hormones play an important role in the development and maturation of the central nervous symptom and their failure in the prenatal period leading to an irreversible brain damage. Their effect on the brain of adult, however, has not been fully studied. With the discovery of neurogenesis in the adult brain, many recent studies have been focused on the understanding the basic mechanisms controlling this process. Many neurogenesis regulatory genes are not only transcribed but also translated into the blood cells. The goal of our study was to analyze the transcriptional activity of neurogenesis regulatory genes in peripheral blood cells in patients with thyroid pathology.